Pet owner perspectives, motivators and concerns about veterinary biobanking - McEnhill, Richard; Borghese, Holly; Moore, Sarah A. (Frontiers in Veterinary Science, 2024)
Veterinary biobanks store samples for future use and distribute samples to academic researchers and industry entities; however, informed consent provided by owners for pets contributing to biobanks can be complicated by limited understanding of goals, purpose, and logistics of biobanking. This survey-based study aimed to gather feedback from pet owners on how they viewed allowing their pet to contribute to a veterinary biobank, with the goal of identifying opportunities to improve education, awareness of veterinary biobanking initiatives, and the consent processes. An electronic survey was distributed to a listserv of 2,119 pet owners and responses were received from 118 respondents (5.6%). Most respondents (67%) were not familiar with the concept of veterinary biobanking prior to having responded to the survey. Most (89%) were willing to allow their healthy pet to contribute samples to a veterinary biobanking program. Ninety-five percent would allow their sick pet to contribute. Most were neutral about financial incentives as a motivator to participate, although 40% indicated that if their pet's condition resulted in a decision to humanely euthanize, they would be more likely to contribute to the biobank if the veterinary biobanking program covered the cost of the euthanasia. Common concerns included security/confidentiality (36%), that results would not be shared with them (33%) or that samples would be used for other purposes beyond those advertised (22%). These results suggest veterinary biobanking initiatives are well received by owners and most are willing to allow their pets to participate. Respondent concerns represent opportunities for veterinary biobanks to improve messaging and dissemination of results from work they support.